Internalization of Moslem Characteristic in Elementary School: A Self-determination Theory Perspective - Lilis Kurniawati; Muhammad Rafdi Al Huda (Nur Science Institute, 2021)
Background: This study aims to reveal (1) the values ​​of religious characters that are integrated into the learning process, (2) the teacher's strategy in integrating religious values ​​in the learning process, (3) the driving and inhibiting factors in integrating religious values ​​in the learning process at Elementary School (MI) Muhammadiyah Bloran. Method: This is a qualitative case study design. The subjects of this study are teachers and students. Data collection technique used through interview and documentation techniques. Validation of data using triangulation techniques and sources. Data analysis techniques using interactive analysis techniques. Result: The study of result shows that (1) the integration of religious values ​​in the learning process is carried out through the planning, implementation, and evaluation stages. Ten religious values are integrated into the learning process. (2) The strategy of integrating religious values ​​is carried out by giving assignments, observing students in doing assignments, imitating teachers, translating the vision and mission of school with Islamic values ​​in mind in the learning environment, implementing learning programs with Islamic values, providing motivation, giving advice, sanctions, and rewards. (3) The driving factors for integrating values ​​include teachers, parents, and the community in the school environment. While the inhibiting factors are the limitations of infrastructure, the diversity of student characteristics, the presence of provocateurs as well as social interaction in the home environment of students who are not controlled so that it has a bad effect.